UPAYA PENCEGAHAN PERNIKAHAN DINI DENGAN EDUKASI KESEHATAN REPRODUKSI PADA SISWA DI YOGYAKARTA - Haryanti, Priyani; Adiyasa, Ratna Puspita (Universitas Pesantren Tinggi Darul Ulum, 2025)
Background: Early marriage is a national and global issue. The negative impacts of early marriage on adolescents include emotional distress, divorce, suicide, and risky pregnancies. Preliminary studies on social media revealed that the number of marriages among adolescents is increasing every year, with most cases attributed to unintended pregnancies. The author conducted educational sessions with high school students to enhance their knowledge about reproductive health and the prevention of early marriage. Method: Education was provided through discussions and games at a vocational high school in Yogyakarta. Materials on reproductive health and the prevention of early marriage were presented to students using PowerPoint and a sound system. The process included a pre-test, education, post-test, and games, all conducted over a two-hour period. After completion, the evaluation results were analysed using frequency distribution. Results: Education on reproductive health and prevention of early marriage was well received by the students. They actively participated in the process from start to finish, responding to the discussion content. Conclusion: There was an increase in scores before and after education among students at the Cipta Bhakti Husada Health Vocational School in Yogyakarta. Keywords: prevention, early marriage, education, students